1994
DOI: 10.1002/jso.2930560406
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry as a prognostic predictor in gastric linitis plastica

Abstract: The majority of GLP tumors manifest diploid characteristics, and the presence or absence of lymph node metastasis is a major determinant in overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…ence of epidermal growth factor receptor and prognosis. According to Candel et al [26], DNA content correlated significantly with lymph node status, but not with overall survival in 43 surgically treated patients with gastric linitis plastica. Kuniyasu et al [27] reported that amplification of the c-met gene might play a role in carcinogenesis and progression of gastric cancer, especially scirrhoustype gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…ence of epidermal growth factor receptor and prognosis. According to Candel et al [26], DNA content correlated significantly with lymph node status, but not with overall survival in 43 surgically treated patients with gastric linitis plastica. Kuniyasu et al [27] reported that amplification of the c-met gene might play a role in carcinogenesis and progression of gastric cancer, especially scirrhoustype gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DNA aneuploidy was established as an independent prognostic marker in several studies 109–124 . Other studies failed to show such a correlation between ploidy and patient survival at all 125–132 …”
Section: Dna Ploidy and Gastric Adenocarcinomamentioning
confidence: 99%
“…A number of studies demonstrated that DNA aneuploidy is correlated with advanced local tumour extent (pT) 107,119,120,122–124,133 or increased number of lymph node metastases (pN) 102,103,108,109,115,118,120–124,128,131,133,134 . However, other studies failed to prove this association of DNA aneuploidy and tumour progression 101,105,113,117,125,129,130,135 …”
Section: Dna Ploidy and Gastric Adenocarcinomamentioning
confidence: 99%